2010
DOI: 10.3109/09638288.2010.493596
|View full text |Cite
|
Sign up to set email alerts
|

How equitable is vocational rehabilitation in Sweden? A review of evidence on the implementation of a national policy framework

Abstract: Purpose. Under the national framework law in Sweden, all eligible people should have equal chances of receiving vocational rehabilitation. We aimed to review the evidence on (1) whether access to vocational rehabilitation is equitable in practice and (2) whether the outcomes vary for different groups in the population. Method. Systematic review of studies in Sweden that reported diagnostic or socio-demographic characteristics of people offered or taking up rehabilitation programmes and outcomes of such program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
(40 reference statements)
3
27
0
1
Order By: Relevance
“…Our finding, that long sick leave length before referral to the rehabilitation clinic was a strong risk factor for not returning to work, for receiving medical and vocational rehabilitation allowances, and for DP during follow-up is in accordance with the literature [1, 5, 19, 21]. The probability for transition both from and to work during follow-up was highest for those with the shortest sick leave spells, indicating that short sick leave spells may be a risk for new sick leave spells.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our finding, that long sick leave length before referral to the rehabilitation clinic was a strong risk factor for not returning to work, for receiving medical and vocational rehabilitation allowances, and for DP during follow-up is in accordance with the literature [1, 5, 19, 21]. The probability for transition both from and to work during follow-up was highest for those with the shortest sick leave spells, indicating that short sick leave spells may be a risk for new sick leave spells.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we did not find any association between young age and RTW after the rehabilitation program, but it was a higher probability for being on vocational rehabilitation allowance for those with younger age. In a Swedish study, RTW after vocational rehabilitation was found to be higher for the younger age groups, particular for those below 40 years [1]. However, vocational rehabilitation allowance in Norway may differ from vocational rehabilitation Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations